Peran Profitabilitas dan Good Corporate Governance dalam Memediasi Pengaruh Struktur Modal Terhadap Nilai Perusahaan - Imam Mujahidin; luhgiatno luhgiatno; Eman Sukanto (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
This study is about the value of the food and beverage sector manufacturing companies in the Indonesia Stock Exchange from 2013 to 2016. The objective is to analyze the effect of Profitability and Good Corporate Governance in mediating the effect of capital structure on firm value. Methods of data analysis using multiple regression and single test to test the hypothesis. The population in this research are food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. The sample in this study was selected through purposive sampling, so that a sample of 42 companies was obtained. The result of this research is that capital structure has a negative and significant effect on profitability. Capital structure has a positive and significant effect on Good Corporate Governance (GCG). Capital structure has a positive and significant effect on Firm Value. Profitability has a positive and significant effect on Firm Value. Good Corporate Governance (GCG) has a positive and insignificant effect on Company Value. Profitability cannot mediate the relationship between capital structure and firm value. Good Corporate Governance (GCG) cannot mediate the relationship between capital structure and firm value.